Ternary polyurethane nanocomposites with remarkable electrical conductivity. Issue 5 (23rd March 2020) - Al-Attabi, Nuha Y.; Adhikari, Raju; Cass, Peter; Bown, Mark; Kaur, Gagan; Gunatillake, Pathiraja; Malherbe, François; Yu, Aimin
ABSTRACT: A series of polyurethane composites with constant 5 wt-% loading of 2D graphene nanosheets and varying levels of 1D silver nanowire (AgNW) were prepared by a solution mixing method. The electrical conductivity of composite films was measured using a 4-point probe method. An extremely high conductivity of 3, 657 S cm –1 was achieved with a polyurethane composite containing 25 wt-% AgNW and 5 wt-% graphene, confirming that a combination of AgNW and graphene is very effective in producing conducting pathways to achieve high conductivity. The incorporation of AgNW and graphene was confirmed by scanning electron microscopy and energy dispersive spectrometry. Additionally, the results of tensile strengths and thermogravimetric analysis showed that the as-prepared polyurethane composite films possessed good mechanical properties and stable thermal properties.